Integration of Zachman Framework and TOGAF ADM on Academic Information Systems Modeling - Fadlil, Abdul; Riadi, Imam; Basir, Azhar (Universitas Nusantara PGRI Kediri, 2021)
Zachman Framework (ZF) and The Open Group Architecture Framework (TOGAF) are Architecture Frameworks often used in Architecture Enterprise's implementation. Each side of the two architecture Frameworks has advantages and disadvantages. Sekolah Tinggi Manajemen Informatika dan Komputer Muhammadiyah Paguyangan Brebes (STMIK MPB) is a new university established on April 28, 2017; STMIK MPB as a new university has no plans in building an information system. The research will select the parts that exist in the ZF and TOGAF methodologies. The two methods will be combined and compiled to be applied to the Academic Information System modeling or blended methods. These research results are architectural blueprints that can be used as a reference in the development of academic information systems.